Effect of soft carbon black on tribology of deproteinised and polyisoprene rubbers - ELTAYEB, N; NASIR, R (ELSEVIER SCIENCE SA, 2007)
In this work, the tribological properties of deproteinised natural rubber (DPNR) were examined and compared with synthetic cis-1,4-polyisoprene rubber (IR), namely Natsyn 2200. The effect of adding carbon black (CB) (0, 25 and 50phr) to both DPNR and IR on the friction and wear characteristics was investigated. Dry abrasion tests were carried out using pin-on-cylinder tribometer with abrasive paper (Diamond 50) under different operating test conditions such as applied normal load (5-35 N), sliding speed (0.3-1.5 m/s) and sliding distance (90-450 m).